Efeito agudo de uma intervenção com exercícios de força muscular em cadeia cinética aberta e fechada no controle postural e na potência muscular em idosos: um ensaio clínico randomizado - Farina, Giovanni Rampinelli (2023)
Ageing causes changes in postural control and muscle function, manifested by an increase in body oscillations and a reduction in muscle power. However, the literature shows that muscle strength exercises are capable of attenuating these impairments. Forms of muscle strength intervention can be classified as open kinetic chain (OKC) and closed kinetic chain (CKC), but despite the biomechanical differences, few studies have investigated the effect of these interventions on postural control and muscle power in the elderly. The aim of this study was to investigate the acute effect of a OKC and CKC strength intervention on postural control performance and muscle power production in the elderly. Twenty-nine people took part in the study and were divided into three groups: OCKG (n=10; 65.7±2.5 years), CKCG (n=10; 67.3±7.3 years) and control group (CG) (n=9; 65.1±5.6 years). Postural control was assessed on a force platform based on center of pressure (COP) oscillation variables - mean displacement amplitude, mean oscillation velocity, oscillation frequency (50% of the spectrum) and peak spectral frequency in the anteroposterior and mediolateral directions - in bipodal, semi-tandem and unipodal support conditions. Muscle power was assessed based on the time taken to perform the Sit-to-Stand (STS) test. All evaluations were carried out before and after an acute intervention with muscle strength exercises in OCK and CKC. Multivariate analyses and delta calculations were used to check for possible group and condition effects, with a significance level of p≤0.05. The results revealed no group differences for the postural control variables. However, there was a difference between CG and CKCG for the time taken to perform the STS test, with the shortest time at the post-intervention moment for the CKCG participants. In addition, a difference was found in the postural control variables between the support conditions, with the greatest COP oscillations present in the unipodal task. Thus, it can be concluded that an acute intervention in OKC and CKC was not enough to differentiate postural balance and muscle power in the elderly. However, CKC exercises were more effective for functional tasks involving lower limb muscles than OKC exercises. Furthermore, it was concluded that the elderly are more prone to postural imbalances when subjected to more complex tasks.